أثر البيئة في أعطال الشبكات الكهربائية في المنطقة الساحلية - محمد زهيرة (Tishreen University, 2019)
تمت في هذا البحث دراسة أثر الظروف البيئية المحيطة في الأعطال التي حدثت على الشبكات الكهربائية 220 kV 66 kV, 20 kV الممددة في المنطقة الساحلية، وذلك برصد الأعطال خلال الفترة من 1985إلى7 199، مع أخذ الشروط الجوية السائدة في المنطقة (رطوبة - مطر - درجة حرارة الوسط الخارجي - سرعة الريح - انفراغات برقية - حالة الجو: غائم، مشمس) بعين الاعتبار. وبينت النتائج الإحصائية أن أغلب الأعطال على شبكات 220 kV, 66 kV حدثت في فصل الصيف، خلال ساعات الصباح الباكر، بين الساعة الثانية والسادسة صباحاً، مما يدل على أن سبب هذه الأعطال يعود إلى انحلال الأوساخ المتراكمة على العازل نتيجة الرطوبة  والندى، كذلك بينت نتائج هذه الدراسة أن سبب أغلب الأعطال التي تحدث في شبكات 20 kV يعود إلى الانفراغات البرقية. وبينت نتائج الدراسة أن انهيار المحولات يتم على مدار ساعات اليوم، وأن عدد المحولات المنهارة في الريف خلال فصل الشتاء، أكبر من عدد المحولات المنهارة في المدينة في الفصل نفسه، وعلى العكس من ذلك خلال فصل الصيف كذلك فإن عدد المحولات المنهارة المتوضعة على أبراج خشبية، يزيد عن عدد المحولات المنهارة المتوضعة على أبراج معدنية. وللمقارنة تم أخذ عدد المحولات المنهارة في حلب وتوزعها خلال الفترة نفسها، مع أخذ الظروف الجوية بعين الاعتبار، وأخذت هاتان المنطقتان لاختلاف ظروفهما المناخية. وقد بينت النتائج أن عدد المحولات المنهارة في اللاذقية يزيد عن عدد المحولات المنهارة في حلب، خلال فصل الشتاء، وتقل عنها في أشهر الصيف. ولدراسة أثر نوع الأبراج على انهيار المحولات تم أخذ خط 20 kV، الذي يصل بين محطة تحويل السن وقرية عين الشرقية، حيث يمتد الخط على أبراج خشبية في منطقة تكثر فيها الانفراغات البرقية. وبعد تأريض العوارض المعدنية الحاملة للعوازل لاحظنا تناقص عدد الأعطال على الخط بشكل كبير. In this research, the effect of environment on electric network faults in the coastal area has been studied. The network voltage levels understudy are 20 kV, 66 kV and 220 kV. The study has been performed by observing the faults between the 1985 to 1997 by taking into account the atmospheric conditions in this area (moisture, rain, outside temperature, the wind speed, lightning discharges and atmospheric situation, cloudy or sunny). Most of the faults occur during early hours in the morning (between two and six). This shows that the occurrence of the faults are because of the decaying of dirt on the insulator by the cause of moisture. Also the results of these studies show that the reason of most faults which happen in the networks 20 kV are related to the lightning discharges. The results of studies show that the transformer breakdown happen during all day. The number of broken down transformers in the countryside during winter is greater than those in the towns in the same season. The opposite happens during summer. The number of failure transformers located on wood poles exceeds the numbers of failed transformers which are located on metal towers. We have studied the numbers and distribution of the faulty transformers in Aleppo in the same period taking into consideration the atmospherical circumstances. These two regions are considered for the differences in their atmospherical circumstances. The results show that the number of broken down transformers in Lattakia exceeds the numbers of broken down transformers in Aleppo during the winter and is less in summer. To study the effect of towers on the transformers faults, the line 20 kV which connects between Elsin transformation station and the village of Ain El-sharqi is considered. This line is located on wood poles in a region where lightning discharges frequently occur. The number of faults is less after earthing the metal girdle which carried the insulators.